Comparison of Sperm Functional Parameters after Cryopreservation of Human Sperm in Three Different Media - S., Sindhuja N.; G., Manjula; N., Sanjeeva Reddy (International Journal of Innovative Research in Medical Science, 2019)
Semen cryopreservation is an integral part of infertility treatment in the current day scenario. Recovery of an optimal number of functionally intact spermatozoa from thawed samples has always been the main objective of semen cryopreservation technology. The aim of this study was to compare of Commercial freezing media with Glycerol egg yolk citrate and Soy lecithin media for the cryopreservation of human spermatozoa. This prospective observational study was done at the department of reproductive medicine and surgery, Sri Ramachandra University during the period of August 2015 to January 2016. Male partner of the infertile couple visiting OPD for infertility treatment with normal semen quality (Normozoospermic) were included in the study. Each semen sample was divided into three aliquots and frozen with Commercial media, Glycerol Egg Yolk Citrate (GEYC) media and soy lecithin media. Semen analysis and sperm function tests before freezing and after thawing namely Acrosome reaction, Capacitation and Mitochondrial potential was compared between the groups. There was a significant decline in motility, vitality and functional parameters of the sperms compared to fresh and frozen thawed in all the groups. However, among the frozen thawed groups, the commercial media and GEYC media were comparable in motility and viability parameters;GEYC media was superior to Commercial media in functional sperm parameter maintenance.